Pengaruh Keterlibatan Pada Program Kampus Mengajar Terhadap Kemampuan Mengajar Mahasiswa Pendidikan Bahasa Korea - Rahma, Nafa Aulia; Samsudin, Didin; Lubis, Arif Husein (Peneliti.net, 2025)
The Merdeka Belajar Kampus Merdeka program is considered useful for developing students' practical and interpersonal skills. This study aims to determine the level of involvement, teaching skills, and explain the impact of the Kampus Mengajar program on the teaching skills of Korean Language Education students. This study uses Kahn's involvement theory and Paquay & Wagner's teaching skills theory. This research used quantitative and qualitative with data collection techniques including questionnaires and interviews. This study involved 39 students who had completed the Kampus Mengajar program. The data were analyzed using simple linear regression, followed by qualitative analysis. The results showed the influence of the Kampus Mengajar program on the students' teaching skills. The level of involvement of Korean Language Education students is categorized as high (79.52%) and the level of students' teaching skills after participating in the program is categorized as high as well (78.47%). The t-test results showed a significance of 0.01 <0.05, indicating the influence of the Kampus Mengajar program on the teaching ability of Korean Language Education students. These results are reinforced by interview data where the process of their involvement in the classroom enriches their knowledge, experience, as well as their teaching skills.